Potential lethal damage repair in glioblastoma cells irradiated with ion beams of various types and levels of linear energy transfer - Chew, Ming Tsuey *; Nisbet, Andrew *; Suzuki, Masao; Matsufuji, Naruhiro; Murakami, Takeshi; Jones, Bleddyn; Bradley, David A (Oxford University Press, 2018)
Glioblastoma (GBM), a Grade IV brain tumour, is a well-known radioresistant cancer. To investigate one of the causes of radioresistance, we studied the capacity for potential lethal damage repair (PLDR) of three altered strains of GBM: T98G, U87 and LN18, irradiated with various ions and various levels of linear energy transfer (LET). The GBM cells were exposed to 12C and 28Si ion beams with LETs of 55, 100 and 200 keV/μm, and with X-ray beams of 1.7 keV/μm. Mono-energetic 12C ions and 28Si ions were generated by the Heavy Ion Medical Accelerator at the National Institute of Radiological Science, Chiba, Japan. Clonogenic assays were used to determine cell inactivation. The ability of the cells to repair potential lethal damage was demonstrated by allowing one identical set of irradiated cells to repair for 24 h before subplating. The results show there is definite PLDR with X-rays, some evidence of PLDR at 55 keV/μm, and minimal PLDR at 100 keV/μm. There is no observable PLDR at 200 keV/μm. This is the first study, to the authors’ knowledge, demonstrating the capability of GBM cells to repair potential lethal damage following charged ion irradiations. It is concluded that a GBM’s PLDR is dependent on LET, dose and GBM strain; and the more radioresistant the cell strain, the greater the PLDR.